The end of AIDS? HIV and the new landscape of illness in rural South Africa - Sanyu A. Mojola; Nicole Angotti; Danielle Denardo; Enid Schatz; F. Xavier Gómez Olivé (Taylor & Francis Group, 2022)
ABSTRACTThe global HIV/AIDS scientific community has begun to hail the dawn of 'the End of AIDS' with widespread anti-retroviral therapy (ART) and dramatic declines in AIDS-related mortality. Drawing on community focus groups and in-depth individual interviews conducted in rural South Africa, we examine the complex unfolding of the end of AIDS in a hard-hit setting. We find that while widespread ART has led to declines in AIDS-related deaths, stigma persists and is now freshly motivated. We argue that the shifting landscape of illness in the community has produced a new interpretive lens through which to view living with HIV and dying from AIDS. Most adults have one or more chronic illnesses, and ART-managed HIV is now considered a preferred diagnosis because it is seen as easier to manage, more responsive to medication, and less dangerous compared to diseases like cancer, hypertension, and diabetes. Viewed through this comparative lens, dying from AIDS elicits stigmatising individual blame. We find that blame persists despite community acknowledgement of structural barriers to ART adherence. Setting the ending of AIDS within its wider health context sheds light on the complexities of the epidemiological and health transitions underway in much of the developing world.